Perbedaan Efektifitas Breathing exercise dan Batuk Efektif terhadap Peningkatan Ekspansi Paru Penderita TB Paru - Rinarto, Nisha Dharmayanti; Setiadi, Setiadi; Sari, Ninik Ambar (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2021)
Introduction: Â Pulmonary TB is a contagious disease in the respiratory system caused by the bacterium Mycobacteria tuberculosis. The purpose of this research is to analyze the difference in the effectiveness of breathing exercise and effective cough to increase lung expansion of pulmonary tuberculosis patients. Objectives: the purpose of this research is to analyze the difference in the effectiveness of breathing exercise and effective cough to increase lung expansion of pulmonary tuberculosis patients. Methods: The research design used Quasy experiment with a Pre-postes approach with a control group design. The population of this research was pulmonary TB patients at Perak Timur Surabaya Public Health Center amounting to 33 people. The sampling technique used Probability Sampling with Simple Random Sampling got a sample of 30 people. Independent variables were aromatherapy eucalyptus oil and breathing exercises. The dependent variable was pulmonary expansion in pulmonary tuberculosis patients. Instrumen in this research used Peak Flow Meter and an observation sheet. Data analysis used the One Way Annova Test. One Way Annova test results showed that breathing exercise was more effective when compared with aromatherapy eucalyptus oil in influencing the process of increasing pulmonary expansion in patients with pulmonary tuberculosis. Results: Â Results of aromatherapy analysis of eucalyptus oil with pulmonary expansion Ï = 0,530 (Ï Ëƒ Î± = 0,05), and breathing exercise with pulmonary expansion Ï = 0.026 (Ï < Î± = 0,05. Conclusions: Â The implications of the study show that breathing exercise is more effective for non pharmacology therapy to help increase lung expansion in patients with pulmonary tuberculosis so as to reduce shortness of breath.